A Comparative Study of Sustainable Cooling Approaches: Evaluating the Performance of Natural Ventilation Strategies in Arid and Semi-Arid Regions - Ahmad Walid Ayoobi; Betül Gelengül Ekimci; Mehmet Inceoğlu (Buildings)
The rising demand for building cooling has led to increased energy consumption and environmental concerns. This study aims to examine the effectiveness of natural ventilation strategies as sustainable approaches in arid and semi-arid climates, focusing on Kabul City. Employing integrated simulation techniques, including annual energy simulation and Computational Fluid Dynamics (CFD) analysis, various ventilation approaches were evaluated, such as single-side ventilation, cross-ventilation, and windcatchers. Results indicate that cross-ventilation with opposing windows significantly outperformed other strategies in terms of natural ventilation rates, achieving a 62.5% improvement over single-sided ventilation and a 36% improvement over cross-ventilation with adjacent windows. However, the complex interplay between solar gain and natural ventilation in these climates can lead to increased cooling demand. To address this challenge, integrating south-(S)-facing orientations into both single-sided and cross-ventilated configurations was found to be a balanced and effective approach. These scenarios demonstrated significant total energy savings. Among single-sided ventilation, the S-facing scenario achieved an average of 58.3% energy savings. For opposing cross-ventilation, the north-south (NS) scenario yielded 65.6% energy savings. Finally, adjacent cross-ventilation in the east-south (ES) and south-west (SW) scenarios resulted in an average of 51% energy savings. Furthermore, windcatchers, when combined with single-sided ventilation, further enhanced natural ventilation and reduced cooling demand while maintaining nearly consistent heating demand. Optimized rooftop windcatchers improved natural ventilation rates by up to 26.9% and attached windcatchers achieved up to 56.8% improvement. Compared to a baseline, rooftop windcatchers reduced cooling demand by 6.2%, and attached windcatchers by up to 18.7%. The findings of this study highlight the potential of window-based and windcatcher natural ventilation strategies as energy-efficient and balanced approaches for reducing building energy consumption, particularly cooling loads, in arid and semi-arid climates. These insights provide valuable guidance for architects and policymakers seeking to promote sustainable and energy-efficient building practices.